Comparative Analysis of Cost, Quality, and Time on the Productivity of Deep Cement Mixing Work Between Subcontractors in the Probolinggo-Banyuwangi Toll Road Construction Project Section 2 - Muhammad Yusuf Sholihin; Kartono Wibowo; Rifqi Brilyant Arief (Riviera Publishing, 2025)
The Trans Java toll road project at the eastern end connects Probolinggo-Banyuwangi (Probowangi), along 171,516 km. Phase 1 of the Gending-Besuki section is being carried out. This study analyzed the difference in time, cost, and quality of deep cement mixing (DCM) work by 4 subcontractors in section 2 (STA 09+000 - STA 20+200) who carried out soil improvements before landfilling. Quantitative methods are used to compare time, cost, and quality. The results show the completion time of DCM: PT Keller Ground Indonesia (85 days), PT Leekang Jaya Konstruksi (116 days), and PT Geotekindo (31 days). Highest daily productivity: PT Geotekindo (428.63 m³/day), followed by PT Keller Ground Indonesia (280.32 m³/day) and PT Leekang Jaya Konstruksi (277.53 m³/day). The lowest DCM price is PT Geotekindo (IDR 681,296/m³), PT Leekang Jaya Konstruksi (IDR 706,980/m³), and the highest PT Keller Ground Indonesia (IDR 788,437/m³). Quality (UCS) of all subcontractors ? 1 MPa. Efficiency shows that subcontractors with high productivity have faster turnaround times, lower costs, and quality to standards.